1970
DOI: 10.3329/bjar.v35i2.5892
|View full text |Cite
|
Sign up to set email alerts
|

Crop productivity as affected by fertilizer management options in Boro -T.<i>aman</i> cropping pattern at farmers' fields

Abstract: The experiment was conducted at multilocation testing (MLT) site, Sujanagar, Pabna during the year of 2003-2004 to find out a soil test based economically viable fertilizer recommendation for the cropping pattern Boro-T. aman. Six treatments viz., moderate yield goal (MYG), high yield goal (HYG), integrated plant nutrient system (IPNS), recommended fertilizer of FRG' 97 (BARC) guide (RF), farmers' practice (FP), and absolute control were employed for the study. The grain yield of Boro and T. aman rice increase… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 2 publications
0
6
0
Order By: Relevance
“…Achieving food security is a significant challenge facing agricultural development worldwide in addition to the option of solving highly critical problems to ensure alleviation of poverty. Realizing food security and agriculture sustainability is urgently required; therefore, improving many agronomic approaches, which have drastic effects on crop growth and yield, e.g., soil nutrient content, crop nutrient requirements, and soil nutrient balance, is necessary [29]. Among various practices followed by many farmers, some are in need of some improvement, particularly having bad habits regarding the use of a large amount of fertilizers under the inherited knowledge that without applying a large amount of fertilizers they do not maintain high yields.…”
Section: Literature Summarymentioning
confidence: 99%
See 1 more Smart Citation
“…Achieving food security is a significant challenge facing agricultural development worldwide in addition to the option of solving highly critical problems to ensure alleviation of poverty. Realizing food security and agriculture sustainability is urgently required; therefore, improving many agronomic approaches, which have drastic effects on crop growth and yield, e.g., soil nutrient content, crop nutrient requirements, and soil nutrient balance, is necessary [29]. Among various practices followed by many farmers, some are in need of some improvement, particularly having bad habits regarding the use of a large amount of fertilizers under the inherited knowledge that without applying a large amount of fertilizers they do not maintain high yields.…”
Section: Literature Summarymentioning
confidence: 99%
“…In spite of the fact that the application of chemical fertilizers has more advantages than disadvantages, it does not always mean that an increase in crop production must be obtained after their application, because a part of the added fertilizers may not be utilized by crop, as it may temporally remain in the soil or may be lost through volatilization or by leaching to underground water and then result in serious problems and dangers and becomes a source of environmental pollution [29,[37][38][39][40][41][42]. Considering the abovementioned reasons and in addition to high costs and declining profitability, scarcity, and leaching down to the root zone, groundwater contamination becomes the cause of diseases.…”
Section: Literature Summarymentioning
confidence: 99%
“…Several studies have shown that intensive rice-based cropping system including rice-wheat (RW) causes remarkable depletion of soil nutrients and threat to crop productivity [2]. Besides the farmers are following imbalanced use of fertilizers for crop production which leads to degrade soil fertility [3]. Farmers generally use fertilizers on single crop basis, not the cropping system.…”
Section: Introductionmentioning
confidence: 99%
“…Although, rotations has notable effects on soil nutrients content, essentially related to nitrogenfixating (Carpenter-Boggs et al, 2000), several researchers have concluded that there are others effects outside that, which can be clarified by soil mineral contents (Wright, 1990;Bullock, 1992 and; improved soil structure (raimbault & Vyn, 1991); improve nutrient use efficiency (Karlen et al, 1994 andTanaka et al, 2005); increased soil organic matter contents,as a result of large amount of crop residue was left in the soil after harvest (Campbell & Zentner, 1993;Bremer et al, 2008;Adiku et al, 2009;Ali et al, 2010;Zhang et al, 2012 andSexton et al, 2014); also crop rotation can have substantial positive influence on plant nutrients uptake and mitigating the effects of limited nutrient availability of N, p, K and Ca for cereal crops (Bolton et al, 1976;Higgs et al, 1976;Welch, 1976;riedell et al, 1998;Brozyna et al, 2013 andAbdul Quddus et al, 2017). Marginal benefit also can be gained in managing the production of crop residues by adopting crop rotation system as compared with monoculture, when high biomass and crop residue were formed (such as corn) are recommended to sequence with crops that produce more subtle residue similar soybean.…”
Section: Rotations and Soil Nutrient Statusand Availabilitymentioning
confidence: 99%